مفهوم الشعر عند لسان الدين بن الخطيب - فارس, عيسى; محفوض, رامية; ديّوب, طلال (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
مفهوم الشعر من أهم القضايا النقدية التي تعرَّضت لاختلافات متعددة بين النقاد قديماً وحديثاً,وداخل هذا الصراع نال هذا المفهوم اهتماماً كبيراً عند لسان الدين بن الخطيب من خلال نظمه وآرائه النقدية, قدَّمه بطريقة تجاوبت فيها خبرة الشاعر مع ثقافة الناقد, وأكد فيه على شمولية هذا المفهوم وإدراكه لأبعاده الزائدة عن الوزن والقافية, معتمداً على عنصر التخييل كفن بلاغي يصل فيه الشاعر إلى مرحلة الخلق والإبداع,وحسن الاختيار, والتأثير والغرابة الفنية,والميل إلى النقد الأخلاقي, ومحاكاة أساليب القدماء في طريقة التعبير والأداء, والإشادة بالطبع والتدفق, ذلك كله يشكل مقولات نقدية فنية سعى لسان الدين بن الخطيب لتطبيقها شاعراً وناقداً. The concept of poetry is one of the most important controversial and critical issues, which caused many disputes among critics in old and late times. Lissan Al-Deen Ibin Al Khatib was greatly concerned with this concept; and this was demonstrated and illustrated through his composition of poetry and his critical ideas. He presented and introduced this concept in such a way that his experience as a poet responded with his education as a critic. He stressed the comprehensiveness of this concept and realized its dimensions which go beyond rhythm and meter, depending upon the element of imagination as a rhetorical art in which the poet comes to the stage of creation and innovation as well as the choice, influence, and artistic queerness. He tends towards ethical criticism and the imitation of old poets in their expression performance and praising Natural mood / disposition and fluency. All these constitute artistic critical sayings which Lissan Al Deen Al Khatib sought to apply as a poet and a Critic.